(untitled) (Medical Forum Monthly, 2020)
Objective: To compare the severity and outcome of acute pancreatitis by comparing the CLI and computed tomography, the serum C-reactive protein and neutrophil levels. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Department of General Surgery, Pakistan Institute of Medical Sciences Islamabad from June 2016 to June 2020. Materials and Methods: A total of 354 patients were enrolled. All patients > 18 years, with confirmed diagnosis of AP were eligible to take part in the study. Patients with symptoms for more than 3 months at the time of data collection were excluded from the study. Complete clinical history and examination were performed on all patients. An improved abdominal computed tomography test was carried out intravenously for pancreas status assessment and computed tomography severity index (CTSI) measurement in these patients. Both patients were also tested on a neurological basis in addition to CTSI, neutrophil-lymphocyte ratio (NLR) and C-reactive protein (CRP). The length of hospital stay, ICU admission and hospital mortality have been measured for the seriousness of acute pancreatitis. Results: The mean age of 54.5±12.4 years. The most frequent etiology of acute pancreatitis was gallstone, 195 (55.1%) followed by infection in 79 (22.32%) and hyperlipidemia in 50 (14.12%) of the patients. The majority of the patients (84;53.8%) with a CTSI score between 7-10 were hospitalized for more than two weeks. Hospital mortality within 72 hours was most frequent in patients who scored higher on CTSI. Out of the 25 patients who expired, 8 (32%) had moderate acute pancreatitis while 15 (60%) had severe acute pancreatitis. Neutrophil to leukocyte ratio and C-reactive protein were both more frequently elevated in patients with severe acute pancreatitis as assessed by hospital stay, ICU admission, and hospital mortality. Conclusion: Computed tomography severity index and C-reactive protein were better predictors of patient severity and outcome while neutrophil-lymphocyte ratio did not seem to differ with the severity of the disease.